At a General Assembly of the governor and Company of the colony of Connecticut, holden at Hartford, on the second Thursday of May 1776 : whereas the General Assembly of this colony, have at this session, enacted, that one regiment or battalion of troops, shall be forthwith raised by voluntary inlistment ... For the encouragement of such ablebodied, effective men ... it is resolved . ([publisher not identified], 1776)
May 9, 1776 Act by the Connecticut General Assembly to raise troops following a request of the Continental Congress. The act provided monetary and other incentives for volunteers to join the Army.